STRATEGI PENGEMBANGAN PASAR AGUS SALIM DI KOTA PEKANBARU - Agustina Stefany Silvianica; Abdul Sadad (Cross-border, 2022)
Pekanbaru City is a city that is actively carrying out development in various fields. The economic activity of the community and the lifestyle of the people of Pekanbaru City have also increased with the increase in industrial development in the city of Pekanbaru. As a result, the city government builds tourist attractions to attract people with different nuances, for example, the night culinary tour which was just built by the government in the city of Pekanbaru, precisely on Jalan Haji Agus Salim. However, unfortunately the development of the market is still in the development and development stage. The study was conducted to analyze the internal-external factors of the development of the Agus Salim market into a night culinary market in the city of Pekanbaru with the nuances of Malay culture typical of Riau. This research involves the method of quality and quantity, the quality method is used to describe the internal-external factors of culinary market development. After that, to formulate the strategy, the researcher used ephas-ifas calculation, SWOT quadrant determination, IE matrix and SWOT analysis. Methods of data collection is done by interviewing and filling out a questionnaire. The results show that the night culinary market of Pekanbaru City is in the second quadrant (Diversification) and based on the IE matrix is in cell 5. The formulation of a strategy that can be applied by the government to develop a typical Malay Riau night culinary market in Pekanbaru City is 1) Build a culinary tourism market that is different from the existing ones and has its own characteristics. 2) Provide complete facilities, for the convenience of the market, for traders and visitors who come. 3) The development and expansion of the market location is very much needed, to be more effective.